PENGARUH LIKUIDITAS, SOLVABILITAS, PROFITABILITAS DAN AKTIVITAS TERHADAP PRICE EARNING RATIO - Ula, Syarifatul; Widodo, Tri; Pramono, Joko; Puspita, Maria Entina (Perwira Journal of Economics & Business, 2024)
The aim of this research is to determine the effect of liquidity, solvency, profitability and activity on price earning ratios in food and beverage companies, either partially or simultaneously. The data used is secondary data published by the Indonesian Stock Exchange in 2022. The research type is explanatory research with multiple linear regression data analysis, t test, F test and coefficient of determination. Based on the partial test the results showed that the Liquidity, Solvency and Activity variable had no significant effect on the price earnings ratio. Profitability variable has a significant effect on the price earnings ratio. In the results of the simultaneous test, there is a significant influence of the variables liquidity, solvency, profitability and activity simultaneously on the price earning ratio of food and beverage companies on the Indonesia Stock Exchange. The coefficient of determination results obtained were 15.5%, these four variables influenced the price earning ratio, while 84.5% were influenced by other variables not examined in this research such as cash ratio, debt ratio, gross profit margin, total assets and turnover ratio. As an investor, you can optimize current assets, apart from that, investors can also increase the company's capital and profits. For further research, it is recommended to use companies from other sectors to obtain variations in research results.